Dr. Sonia Skarlatos and the National Heart, Lung, and Blood Institute Translational Research and Resource Programs - McDonald, Cheryl L. (Mary Ann Liebert, Inc., 2013)
Sonia I. Skarlatos, PhD (September 28, 1953–August 6, 2013), was the deputy director of the Division of Cardiovascular Sciences at the National Heart, Lung, and Blood Institute (NHLBI). This article reviews her work in establishing, leading, or facilitating extramural translational research programs supported by the NHLBI, specifically focusing on her work as a consistent advocate for the advancement of gene and cell therapies.